Penguatan Literasi Membaca Melalui Program Satu Hari Satu Cerita Pada Siswa Kelas V SD Negeri Jabong Kabupaten Subang - Raisha Audi Karyamin; Aulia Mustika Dewi; Neisya Zahira; Arief Destya Rochman; Irpan Maulana (Pusmedia Group Indonesia, 2026)
Low reading literacy skills are a problem faced by fifth-grade students at SDN Jabong, particularly in understanding the content of texts and retelling stories they have read. Students tend to read mechanically without adequate understanding of the story’s elements and moral message. This community service activity aims to improve students’ reading literacy skills by strengthening their understanding of story content and their retelling abilities. The implementation method consists of three stages: presenting material on the definition and elements of a story; screening a children’s story video titled “Si Itik Buruk Rupa” (The Ugly Duckling), followed by a question-and-answer session about the story’s content; and a retelling activity in front of the class. The activity involved 32 fifth-grade students as participants. The results showed that 18 of the 32 students actively participated, and all were able to answer questions accurately and retell the story in a logical and coherent manner. There was a measurable improvement in the students’ understanding of story elements, their ability to draw conclusions, and their confidence in speaking in public. This program proved effective in improving the reading literacy and speaking skills of elementary school students.